A systematic review of interventions to improve medicines optimisation in frail older patients in secondary and acute care settings. (26th March 2021) - Saeed, D; Carter, G; Parsons, C
Abstract: Introduction: Frailty is a geriatric syndrome in which physiological systems have decreased reserve and resistance against stressors. Frailty is associated with polypharmacy, inappropriate prescribing and unfavourable clinical outcomes [1, 2] . Aim: To identify and evaluate studies of interventions designed to optimise the medications of frail older patients, aged 65 years or over, in secondary or acute care settings. Methods: The protocol was registered and published on PROSPERO (CRD42019156623). A literature review was conducted across the following databases and trial registries: Medline, Scopus, Embase, Web of Science, Cochrane Library, Cochrane Central Register of Controlled Trials, International Pharmaceutical Abstracts, Cumulative Index to Nursing and Allied Health Literature Plus (CINAHL Plus), ClinicalTrials.gov, International Clinical Trials Registry Platform and Research Registry. All types of randomised controlled trials (RCTs) and non-randomised studies (NRSs) of interventions relating to any aspect of 'medicines optimisation', 'medicines management' or 'pharmaceutical care' to frail older inpatients (aged ≥ 65 years) were included. Eligible studies published in English were identified from the date of inception to October 2020. Screening and selection of titles, abstracts and full texts were followed by data extraction. Risk of bias was assessed using the Cochrane Collaboration ROB 2.0 tool for RCTs and risk of bias in non-randomized studies-of Interventions (ROBINS-I) tool for NRSs. Results: 36 articles were identified and of these, three were eligible for inclusion (Figure 1). All included studies were RCTs. Although all included studies examined the effect of different types of interventions on different outcomes, they all concluded that medication optimisation interventions reduced suboptimal prescribing (measured as polypharmacy, inappropriate prescribing, and underuse) among frail older inpatients. The included studies used different tools to assess prescribing appropriateness; one used the STOPP criteria, one used STOPPFrail criteria and one employed inpatient/ outpatient geriatric evaluation and management according to published guidelines and Veterans Affairs (VA) hospital standards. Two of the included studies was assessed as having 'some concerns' of bias, and one was judged to be at 'high risk' of bias. Due to the heterogeneity of the included studies, a meta-analysis was not possible. Conclusion: This systematic review demonstrates that medication optimisation interventions may improve medication appropriateness in frail older inpatients. Limitations include the small number of included studies and the exclusion of non-English language articles. However, this review highlights the paucity of evidence that examines impact of medication optimisation on quality of prescribing and clinical outcomes for frail older inpatients including hospitalisation, falls, quality of life and mortality. High-quality studies are needed to address this gap and to outline the framework of medication optimisation for this vulnerable cohort group. References: 1. Clegg A, Young J, Life S, Rikket MO, Rockwood K. Frailty in Older People. Lancet. 2013;381(9868):752–62. 2. Fried, L. P. Tangen, C. M.Walston, J.Newman, A. B.Hirsch, C.Gottdiener et al. Frailty in older adults: evidence for a phenotype. J Gerontol A Biol Sci Med Sci. 2011; 56(3), 146–M15